Climate change impacts and costs to U.S. electricity transmission and distribution infrastructure. (15th March 2020) - Fant, Charles; Boehlert, Brent; Strzepek, Kenneth; Larsen, Peter; White, Alisa; Gulati, Sahil; Li, Yue; Martinich, Jeremy
Abstract: This study presents a screening-level analysis of the impacts of climate change on electricity transmission and distribution infrastructure of the U.S. In particular, the model identifies changes in performance and longevity of physical infrastructure such as power poles and transformers, and quantifies these impacts in economic terms. This analysis was evaluated for the contiguous U.S, using five general circulation models (GCMs) under two greenhouse gas emission scenarios, to analyze changes in damage and cost from the baseline period to the end of the century with three different adaptation strategies. Total infrastructure costs were found to rise considerably, with annual climate change expenditures increasing by as much as 25%. The results demonstrate that climate impacts will likely be substantial, though this analysis only captures a portion of the total potential impacts. A proactive adaptation strategy resulted in the expected costs of climate change being reduced by as much as 50% by 2090, compared to a scenario without adaptation. Impacts vary across the contiguous U.S. with the highest impacts in parts of the Southeast and Northwest. Improvements and extensions to this analysis would help better inform climate resiliency policies and utility-level planning for the future. Highlights: Infrastructure expenditures may rise as much as 25% due to climate change alone. Smart adaptation reduces expected costs by as much as 50% by 2090. Highest costs related to substation lifespan and vegetation management. Southeast and Northwest of the U.S. are the most vulnerable regions.